Dielectric, magnetic and structural characterizations in Mn doped 0.9BiFeO3-0.1BaTiO3 compositions. (3rd October 2018) - Gotardo, Ricardo; Silva, Everton; Alonso, Raquel; Rosso, Jaciele; Silva, Daniel; Santos, Guilherme; Silva, Klebson; Cótica, Luiz; Santos, Ivair; Guo, Ruyan; Bhalla, Amar
Abstract: In this work, we reported investigations on the structural, magnetic and dielectric properties of Mn doped 0.9BiFeO3 -0.1BaTiO3 multiferroic compounds. X-ray diffraction studies revealed that the materials crystallized in a pure distorted rhombohedral perovskite structure. A significant magnetization increase (reaching 0.50 emu/g) was observed for Mn - doped samples. The dielectric characterization revealed that for the un-doped sample two conductivity mechanisms are present, one starting around 177 K and other around 325 K. In the doped samples, however, one of these mechanisms was suppressed increasing the resistivity and decreasing the dielectric losses of the samples.